The Unraveling of K-12 Program as an Education Reform in the Philippines - Abulencia, Arthur S (SIPATAHOENAN, 2015)
ABSTRACT: Education is big social investment for families or parents as well as the entire nation. We cannot afford to have a good or quality education, even at least the basic level. Although the true aim of education is to nurture human being to become truly human being, however because of global competition, we need to educate and train our students to be at par with their counterparts in other parts of the world. And, of course, we need them to be parts or contributors to develop our national economy. In the context of the Philippines, it is relevance to note here that more than two years ago, the incumbent President Aquino signed into law the Basic Education Act of 2013 (Republic Act 10533), or most commonly referred to as K-12 Program. The K-12 Program mandates that all pupils entering Grade 1 should have compulsory undergone kindergarten or pre-school, and the secondary level will add two more years, that is the senior high school. Accordingly, everybody has stake or concern about education, and, consequently, we should listen to all the voices who are uttering their piece regarding the K-12 Program. There are beneficiaries of the K-12 Program, but some sectors will be drastically affected and dislodged. We should have an open eye and listening ear to consider and integrate the ideas and suggestions of people.KEY WORD: K-12 Program; Education Reform; Quality Education; Global Competition; Ideas and Suggestions of people.Â INTISARI: âMengurai Program K-12 sebagai Reformasi Pendidikan di Filipinaâ. Pendidikan adalah investasi sosial yang besar untuk keluarga atau orang tua serta seluruh bangsa. Kita tidak mampu untuk memiliki pendidikan yang baik atau kualitas, bahkan setidaknya pada tingkat pendidikan dasar. Meskipun tujuan sebenarnya dari pendidikan adalah untuk membina manusia menjadi makhluk yang benar-benar manusiawi, namun karena persaingan global, kita perlu mendidik dan melatih para siswa agar menjadi setara dengan rekan-rekan mereka di bagian lain dunia. Dan, tentu saja, kita membutuhkan mereka untuk menjadi bagian atau kontributor untuk mengembangkan perekonomian nasional kita. Dalam konteks Filipina, adalah relevan untuk dicatat di sini bahwa lebih dari dua tahun yang lalu, Presiden petahana Aquino telah menandatangani Undang-Undang Pendidikan Dasar 2013 (Republic Act 10533), atau sering disebut sebagai Program K-12. Program K-12 mengamanatkan bahwa semua murid yang masuk Kelas I wajib menjalani pendidikan TK (Taman Kanak-Kanak) atau pendidikan pra-sekolah, dan sekolah menengah akan ditambah dua tahun lagi, yaitu hingga SMA (Sekolah Menengah Atas). Dengan demikian, setiap orang memiliki modal atau perhatian terhadap pendidikan, dan, akibatnya, kita harus mendengarkan semua suara mereka yang disampaikan secara tidak utuh mengenai Program K-12. Ada manfaat dari Program K-12 ini, namun beberapa sektor kehidupan akan secara drastik dipengaruhi dan dipreteli. Kita harus memiliki mata dan telinga untuk mendengarkan secara terbuka dalam mempertimbangkan dan mengintegrasikan semua ide dan saran dari masyarakat.KATA KUNCI: Program K-12; Reformasi Pendidikan; Pendidikan Berkualitas; Persaingan Global; Gagasan dan Saran dari Masyarakat.About the Author: Assoc. Prof. Dr. Arthur S. Abulencia is a Senior Lecturer at the Faculty of Behavioral and Social Sciences PNU (Philippine Normal University), Taft Avenue, Manila 1000, the Philippines. For academic interests, the author is able to be contacted via his e-mails at: arthurpnu@yahoo.com and abulencia.as@pnu.edu.phHow to cite this article? Abulencia, Arthur S. (2015). âThe Unraveling of K-12 Program as an Education Reform in the Philippinesâ in SIPATAHOENAN: South-East Asian Journal for Youth, Sports & Health Education, Vol.1(2) October, pp.229-240. Bandung, Indonesia: Minda Masagi Press, APAKSI Bandung, and KEMENPORA RI Jakarta, ISSN 2407-7348.Chronicle of the article: Accepted (June 14, 2015); Revised (August 30, 2015); and Published (October 28, 2015).